Winterlight - Britain, Kristen (Britain, Kristen. Green rider (Series), 2021)
After King Zachary sends soldiers and Green Riders to defend a mountain pass, Karigan G'ladheon meets up with the riders and realizes that to become a true Green Rider she must overcome the losses of her past and use her abities to defend Sacoridia.